Hubungan Dukungan Sosial dengan Kepercayaan Diri Mahasiswa dalam Konteks Interaksi Sosial di Lingkungan Perguruan Tinggi - Minggus S. Masela; Bernardus Liat Wungubelen; Alfedro Putut Prahoro; Purborini, Vivi Sylvia (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to examine the relationship between social support and self-confidence among university students within the context of social interactions in the higher education environment. Social support plays an important role in helping students adapt to academic and social demands, which in turn may influence their level of self-confidence. This research employed a quantitative approach using a correlational design. The participants were university students selected through purposive sampling. Data were collected using social support and self-confidence questionnaires, and the data were analyzed using Pearson correlation analysis. The results showed a significant positive relationship between social support and self-confidence, indicating that higher levels of social support are associated with higher self-confidence among students. These findings suggest that social support from peers, family, and the academic environment contributes positively to the development of students’ self-confidence. Therefore, efforts to strengthen social support systems in higher education institutions are important to enhance students’ social and psychological well-being.